Effect of Teams Games Tournament Learning Model Assisted by Question Ball Media on the IPAS Learning Outcomes - Muhamad Nailul Furqon; Siti Masfuah; Erik Aditia Ismaya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Low learning outcomes, especially in IPAS subjects, are often caused by students becoming passive and disengaged in class when learning is dominated by lecture methods (teacher-centered). Thus, the purpose of this study is to investigate how well the Teams Games Tournament (TGT) model, combined with question-ball media, affects fourth-grade students' learning outcomes. In this study, a quantitative, one-group pretest-posttest design was used, with 24 students from SDN 03 Sidigede as the research subjects. The instrument in this study was a validated learning outcome test, and the data analysis involved normality testing and N-Gain analysis using IBM SPSS version 25. According to the analysis, using the TGT model with question-ball media improved student learning outcomes. This is indicated by the N-Gain values in the moderate improvement category for the concept understanding and skills processes, which are 0.57 and 0.54, respectively. These findings indicate that implementing the TGT model with the help of question ball media not only improves learning outcomes but also encourages active student participation in learning, strengthens learning motivation, and helps students understand IPAS concepts more contextually through game activities and group work.